FAKTOR PROGNOSTIK TERHADAP KEJADIAN INFEKSI LUKA OPERASI (ILO) PADA PENDERITA MALFORMASI ANOREKTAL PASCAOPERASI PEMBUATAN ANUS DI RSUP DR. SARDJITO, YOGYAKARTA, PERIODE JANUARI 2008 â DESEMBER 2012 - , Padli ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Surgical Site Infection (SSI) is still a source of morbidity in postsurgical patients. The incidence of SSI is ranging from 500,000 a year at 27 million surgery and a quarter of the cases of nosocomial infections in the US each year. SSI is a postoperative complication anoplasty, besides constipation and incontinence. The incidence of SSI after postoperative anoplasty have not been widely reported. Objective: This is a study to determine factors which have role in a SSI postoperative anoplasty, in the other hand, all factors that contribute to SSI could be diminished and length of stay of these patients could be minimalized. Method: This is a case control study, using medical record from Sardjito Hospital, from January 2008 to December 2012. The different factors then analyzed using chi square with level of significance P<0.05. We used multivariate analysis to find which factor that have the greatest influence on the incidence of SSI. Result: Age at operation, operation technique had significant factors of SSI postoperative anoplasty, with OR 10 (95% CI 1,199 to 83,421)